Pelaksanaan Lesson Study Dalam Pembelajaran SKI Di MTs Darul Ulum Mojosarirejo Driyorejo Gresik - Nanang Sumantri (Pedir Research Institute, 2022)
The background of this research is 1. How is the implementation of lesson study in literacy-based SKI learning at MTs Darul Ulum Mojosarirejo Driyorejo 2. What are the factors that support and hinder the implementation of lesson study in literacy-based SKI learning at MTs Darul Ulum Mojosarirejo Driyorejo Research on analysis Lesson Study in SKI learning uses qualitative descriptive, namely describing, reviewing and linking the data obtained both textually and contextually. The research findings were obtained. First, the implementation of lesson study in SKI learning at MTs Darul Ulum Mojosarirejo Driyorejo Gresik is divided into three stages, namely planning (plan), implementation (do), and reflection (see). The two supporting factors for lesson study include 1) The existence of full support from the Education Unit, especially the Head of Madrasah, making lesson study an approach to academic supervision 2) The open nature of teachers at MTs Darul Ulum to accept each others input and criticism. The three inhibiting factors for lesson study include: 1 ) Time or schedule of Lesson Study activities clash with other teachers' teaching and learning activities. 2) The preparation of model teachers in carrying out Lesson Study is less than optimal. 3) There are teachers who do not want to accept changes or lesson study innovations 4) Limited facilities and infrastructure 5) Enforcement of the Emergency Curriculum during the Covid-19 Pandemic Period.